Regional trade patterns across Africa - Goundan, Anatole; Fall, Cheickh Sadibou (International Food Policy Research Institute, 2018)
Chapter 3, by Anatole Goundan and Cheickh Sadibou Fall, addresses regional trade, discussing Africa-wide and regional trade patterns. The chapter reviews intra-regional trade performance for the continent as a whole and for its major regional economic communities (RECs). It then proceeds to analyze the direction of trade, examine the role of individual RECs and countries in intra-regional trade, and discuss the key commodities in intra-regional trade.